Perancangan Sistem Informasi Persediaan Barang Habis Pakai Berbasis Web pada Disdukcapil Kabupaten Batang - Najwaa Fatikhah Hidayat; Tri Agus Setiawan; Arochman Arochman (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The management of consumable supplies at the Population and Civil Registration Office (Disdukcapil) of Batang Regency is still carried out manually using separate record books and Microsoft Excel, resulting in delays in stock data updates and inefficiencies in reporting. This study aims to design a web-based information system for consumable supply management to support more structured and accountable operations. The study employs an engineering research approach with qualitative descriptive methods and object-oriented analysis. The research informant is a general affairs staff member who is directly involved in consumable supply management, selected purposively as the party most familiar with the existing processes and problems. Data collection instruments include interviews, observation, and documentation; while system design utilizes Unified Modeling Language (UML) modeling. The results of this study are an object-oriented system design equipped with features including a stock summary dashboard, recording of incoming and outgoing stock transactions, online supply requests, stock cards, inventory reports, and minimum stock notifications. Design validation was conducted through the User Walkthrough method involving a key informant at Disdukcapil Batang Regency, and all designed features were declared valid and in accordance with the operational needs of the institution. The study concludes that this system design is capable of improving operational efficiency and accountability in supply management, and full implementation is therefore recommended.